Effect of variety and sulphur on yield and yield components of groundnut: Variety and sulphur effect on groundnut - ., Nurezannat; Sarkar, Md Abdur Rahman; Uddin, Md Romij; Sarker, Uttam Kumer; Kaysar, Md Salahuddin; Saha, Pikon Kumar (Journal of the Bangladesh Agricultural University, 2019)
Variety and sulphur play a significant role in the physiological growth and yield of crops such as groundnut. Even so, there has been little information on the application of variety and sulphur in groundnut. Therefore, an experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University (BAU), Mymensingh to investigate the effect of sulphur on yield and yield components of two groundnut varieties. The experiment comprised two varieties of groundnut viz. BARI Cheenabadam-8 and Bina cheenabadam-6; and five levels of sulphur viz. 0, 15, 30, 45, and 60 kg ha–1. The experiment was laid out in a randomized complete block design with three replications. Among the parameters leaf area index (2.03), dry matter plant–1 (50.36 g), number of primary branches plant–1 (10.33 cm), number of secondary branches plant–1 (9.27 cm), number of pegs plant–1 (46.27), number of total pods plant–1 (37.80), 100-pods weight (96.82 g), 100- seeds weight (46.25 g), shelling percentage (85.29%), pod yield (3.13 t ha–1), seed yield (2.67 t ha–1), stover yield (6.84 t ha–1), and harvest index (31.37 %) were the highest in BARI Cheenabadam-8, when treated with sulphur 60 kg ha–1. The lowest values of all these parameters were found in Binacheenabadam-6, when no sulphur was applied. This study suggested that BARI Cheenabadam-8 combined with sulphur 60 kg ha–1 could be applied for obtaining the highest yield of groundnut. J. Bangladesh Agril. Univ. 17(1): 1–8, March 2019